Current Insights on Percutaneous Coronary Intervention in Non-ST Elevation Acute Coronary Syndrome - Oktaviono, Yudi Her (Heart Science Journal, 2024)
Percutaneous coronary intervention (PCI) is a cornerstone in the management of non-ST elevation acute coronary syndrome (NSTE-ACS), offering significant improvements in patient outcomes. Risk stratification is critical in guiding the urgency and timing of PCI, with invasive strategies recommended for high-risk patients identified by clinical, electrocardiographic, biomarker assessments, or validated scores. Multivessel coronary artery disease is frequently observed in patients with NSTE-ACS and is correlated with an increased likelihood of recurrent myocardial infarction and mortality. Preferably during the index procedure, complete revascularization should be considered in patients with stable hemodynamics. Functional invasive evaluation, including fractional flow reserve, may help assess the hemodynamic significance of coronary lesions and decide whether a non-culprit stenosed vessel prompts revascularization. Intravascular imaging techniques with optical coherence tomography and intravascular ultrasound are essential for evaluating lesion characteristics, optimizing stent deployment, and enhancing the precision of PCI. Overall, a personalized interventional approach in NSTE-ACS incorporating risk stratification, timely intervention, careful consideration of multivessel disease, and advanced diagnostic modalities is paramount in enhancing patient prognosis and minimizing recurrent ischemic events....